Towards Application of Electro-Fermentation for the Production of Value-Added Chemicals From Biomass Feedstocks - Yamada, Shohei; Takamatsu, Yuki; Ikeda, Sota; Kouzuma, Atsushi; Watanabe, Kazuya (Frontiers in Chemistry, 2022)
According to recent social demands for sustainable developments, the value of biomass as feedstocks for chemical industry is increasing. With the aid of metabolic engineering and genome editing, microbial fermentation has been developed for producing value-added chemicals from biomass feedstocks, while further improvements are desired for producing more diverse chemicals and increasing the production efficiency. The major intrinsic limitation in conventional fermentation technologies is associated with the need for balancing the net redox equivalents between substrates and products, resulting in limited repertories of fermentation products. One solution for this limitation would be “electro-fermentation (EF)” that utilizes bioelectrochemical systems for modifying the intracellular redox state of electrochemically active bacteria, thereby overcoming the redox constraint of fermentation. Recent studies have attempted the production of chemicals based on the concept of EF, while its utility has not been sufficiently demonstrated in terms of low production efficiencies. Here we discuss EF in terms of its concept, current status and future directions, which help us develop its practical applications to sustainable chemical industries.